Rural-urban disparities in postpartum contraceptive use among women in Nigeria: a Blinder-Oaxaca decomposition analysis - Obinna Princewill Anyatonwu; Miguel San Sebastián (BMC, 2022)
Abstract Background Unintended pregnancies are a global public health concern that could be prevented with appropriate access to contraceptive methods. Evidence from research has indicated that avoidance of closely space birth/pregnancy within the first year of postpartum, mitigates the risk of adverse health outcomes such as preterm birth, low birth-weight, etc. Postpartum family planning helps women to minimize closely spaced and unplanned pregnancies within the first 12 months after delivery. Less contraceptive use is often present in more socially disadvantaged groups. Studies from Nigeria have shown a persistent disparity on contraceptive use between rural and urban residents. To identify the factors explaining these inequalities is important to implement targeted interventions. This study aimed to identify the factors contributing to the rural-urban disparity in postpartum contraceptive use among women in Nigeria. Methods This is a cross-sectional study using the Nigerian Demographic Health Survey. In total, 28,041 postpartum Nigerian women were included. Self-reported contraceptive use was the outcome, while the selected explanatory variables were grouped according to three theoretical perspectives: materialistic, behavioural/cultural, and psychosocial variables. Descriptive statistics and Blinder-Oaxaca decomposition were used to summarize and identify the factors contributing to the rural-urban disparity in postpartum contraceptive use. Results In this study, 27% of women reported to have used contraceptives during the postpartum period. The rural-urban disparity in postpartum contraceptive use accounted for 18.2 percentage points. The findings further showed that the disparities in postpartum contraceptive use between rural-urban residence were mostly explained by materialistic variables (82%), followed by the behavioural/cultural variables and age (included as covariate) accounting for 15.6 and 3.0%, respectively. Household wealth (37%) and educational attainment (38%) had the most significant contribution to the differences in postpartum contraceptive use. Only 15% of the difference in postpartum contraceptive use remained unexplained. Conclusion This study has shown important inequalities in postpartum contraceptive use between rural and urban residents in Nigeria. These differences were mainly explained by materialistic factors. These findings highlight crucial areas for the government to target in order to close the existing gap between rural and urban settings in contraceptive use in the country.